Kontrol Motor Berbasis PID untuk Pompa Air di Miniatur Rumah Kaca - Himawan, Helmy Mukti; Mustikasari, Vita Ria; Muhammad Fahmi Hakim (Politeknik Negeri Malang, 2024)
Greenhouses are crucial in agriculture for enhancing crop yields by providing controlled environmental conditions. Efficient water management is a key challenge in conventional greenhouse systems, often leading to water wastage due to unmeasured soil moisture levels. This research aimed to design and implement a PID control system for water pumps in a miniature greenhouse to optimize water usage and maintain stable soil moisture and temperature levels. The methodology involved integrating PID control with sensors to monitor and adjust the water pump operation based on real-time soil moisture and temperature data. The study found that the PID-controlled system reduced the time to reach steady-state conditions from 650 ms to 600 ms, with no overshoot compared to systems without control. Additionally, the error in the PID system ranged from 0.89% to 2.32%. These findings suggest that PID control significantly enhances the efficiency and effectiveness of water usage in greenhouses, contributing to better crop management and resource conservation. The implications of this research are substantial for agricultural practices, as it demonstrates a viable solution for improving irrigation precision and overall greenhouse management.